2011
DOI: 10.4103/0378-6323.82408
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of seborrheic keratoses in south Indians: A clinical and dermoscopic study

Abstract: The most common clinical variant of SK was CSK, followed by DPN, PSK, Flat SK, and stucco keratoses. Dermoscopic findings were consistent with those described in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 6 publications
3
13
0
Order By: Relevance
“…has reported the frequency of occurrence of various clinical types of SK, CSK being the most common (60%), followed by DPN (46.6%), pedunculated SK (21.2%), and stucco keratoses (2%). [3] Our study also showed the highest incidence of CSK (46%), followed by DPN (26%). We had a higher incidence of stucco keratoses (18%) compared to pedunculated variety (10%).…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…has reported the frequency of occurrence of various clinical types of SK, CSK being the most common (60%), followed by DPN (46.6%), pedunculated SK (21.2%), and stucco keratoses (2%). [3] Our study also showed the highest incidence of CSK (46%), followed by DPN (26%). We had a higher incidence of stucco keratoses (18%) compared to pedunculated variety (10%).…”
Section: Discussionsupporting
confidence: 65%
“…[6] In some studies, a slight female preponderance of the DPN variant was seen. [3] A female preponderance of 76% seen in our study could be due to the fact that women usually seek dermatological advice due to the cosmetic concern more than men.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations